2015
DOI: 10.1152/ajpheart.00734.2013
|View full text |Cite
|
Sign up to set email alerts
|

Impaired oxidative metabolism and calcium mishandling underlie cardiac dysfunction in a rat model of post-acute isoproterenol-induced cardiomyopathy

Abstract: Stress-induced cardiomyopathy, triggered by acute catecholamine discharge, is a syndrome characterized by transient, apical ballooning linked to acute heart failure and ventricular arrhythmias. Rats receiving an acute isoproterenol (ISO) overdose (OV) suffer cardiac apex ischemia-reperfusion damage and arrhythmia, and then undergo cardiac remodeling and dysfunction. Nevertheless, the subcellular mechanisms underlying cardiac dysfunction after acute damage subsides are not thoroughly understood. To address this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 67 publications
2
47
0
Order By: Relevance
“…Furthermore, ISO reduced hemodynamic parameters (MAP, LVDP, and AEdP/dt max ) and increased the infarct area. Taken together, ISO induces an acute MI and, additionally, induced mitochondrial dysfunction-including impaired oxidative metabolism, calcium mishandling [42], decreased mitochondrial bioenergetics and enhanced oxidative stress [43], but the effects on mitochondrial dynamics were rare.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ISO reduced hemodynamic parameters (MAP, LVDP, and AEdP/dt max ) and increased the infarct area. Taken together, ISO induces an acute MI and, additionally, induced mitochondrial dysfunction-including impaired oxidative metabolism, calcium mishandling [42], decreased mitochondrial bioenergetics and enhanced oxidative stress [43], but the effects on mitochondrial dynamics were rare.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Ca 2+ levels in cardiac cells are coregulated by both ERs and βARs. Numerous studies provide compelling evidence that oestrogen influences the expression levels of Ca 2+ ‐handling proteins, whose functions are primarily under the regulation of βARs (Figure ) . In addition to the major proteins LTCC, RyR, PLB, SERCA and NCX, sarcolipin (SLN), an inhibitor of SERCA, plays a role in cardiac Ca 2+ handling .…”
Section: Ers and βArs As Coregulators Of Cardiac Ca2+‐handling Proteinsmentioning
confidence: 99%
“…25,55 These conclusions have been strengthened further from the findings of Willis et al, who demonstrated in an animal model the contractile dysfunction in TTS is a consequence of mitochondrial impairment, with decreased ATP synthesis capacity and increased reactive oxygen species (ROS) production. 56 However, these metabolic derangements and energetics impairment also occur in heart failure irrespective of the disease etiology and what remains to be known how exactly the metabolic derangement in TTS is different from the conventional heart failure.…”
Section: Future Directions -Possible Targets For Interventionmentioning
confidence: 99%